Development of a device based on the respirometric principle for long-term monitoring of BOD and pH: a novel approach in wastewater characterisation - Thanh Dam Nguyen; My Linh Hoang; Hong Anh Duong; Hung Viet Pham; Anh Tuan Do; Jean-Luc Vasel (Vietnam Journal of Science, Technology and Engineering, 2020)
Biochemical oxygen demand (BOD) and pH are two important parameters in environmental analysis that allow the assessment of water quality. Although the long-term determination of BOD and pH can provide more useful information about the wastewater characteristics, present commercial BOD devices do not usually meet this demand. This research has successfully developed a novel BOD/pH device based on the respirometric principle, which can simultaneously and continuously monitor both BOD and pH of wastewater for about 20 days. The performance of the proposed device is evaluated in the laboratory by comparison to that of a commercial device (BOD Trak II, HACH). This solution not only follows the variation of BOD and pH over a long period of time, but also shows low cost and high potential for a wide variety of applications in Vietnam.